Fulfillment of Women's Basic Rights in the Correctional System at Class II A Sungguminasa Women's Prison (JED (Jurnal Etika Demokrasi), 2025)
This study addresses the critical issue of bridging the gap between legal guarantees and practical fulfillment of women’s rights in Indonesian prisons, focusing on the Class II A Sungguminasa Women’s Prison. The research aims to evaluate the extent to which basic rights—such as health care, nutrition, protection, and development—are realized for incarcerated women within the framework of national law and international standards. Employing a qualitative descriptive approach, the study involved in-depth interviews, participant observation, and document analysis, with a purposive sample of female inmates and correctional staff. Data were analyzed using the Miles and Huberman interactive model to ensure rigor and credibility. Findings indicate that the institution has made significant progress in providing comprehensive health services, tailored nutrition, secure and protective environments, and relevant rehabilitation programs. These advances reflect effective translation of regulatory ideals into operational practice, though some challenges in sustainability and resource allocation persist. The study concludes that a holistic, rights-based approach can substantially enhance gender-sensitive correctional services. The novelty of this research lies in its integrative assessment of rights fulfillment, highlighting the interaction of legal frameworks, institutional adaptation, and lived experiences. The study’s contribution provides evidence-based guidance for policy development and scholarly discourse on gender justice and correctional reform in Indonesia and similar contexts.
Keywords: Women’s Rights; Correctional Institutions; Gender Equality; Qualitative Research; Indonesia